Epidemiologic, clinical findings and risk factors of recurrent herpes labialis in healthy adult patients: a case-control study - Nassaji, Mohammad; Ghorbani, Raheb; Taheri, Ramin; Azizzadeh, Maryam; Abbassyan, Fatemeh (The European Research Journal, 2019)
Objectives: Herpes labialis is a common viral infection and characterized by recurrent vesicular lesion primarily on the lips and perioral skin. The aim of this study was to determine the epidemiological, clinical characteristics and trigger factors associated with recurrence herpes labialis in adult patients. Methods: This case-control study was conducted with the participation of one hundred adult patients and the same number of control. Data collected about demographics, clinical, as well as trigger factors from individuals who met inclusion criteria. Results: Seventy-four percent of cases and 34% of controls were female that showed significant difference (p < 0.001). Mean body mass index of patients was significantly higher than controls (25.9 ± 2.9 kg/m2 versus 22.0 ± 2.9 kg/m2, p < 0.001). The most common location of the lesions during the last episode of infection was upper lip (65%). The number of lesions was single in 58% and multiple in 42% of patients. The frequency of episodes per year was more than two attacks each year in most patients (83%). Positive family history of recurrence herpes labialis was found in 50% and 20% of cases and controls respectively (p < 0.001). Emotional stress (61%), sunlight exposure (54%) and flu (37%) were the main triggering factors reported by the patients. Conclusions: This study revealed that recurrence herpes labialis is more common in women and on the upper lip. Family history of recurrence herpes labialis was positive significantly in patients. The most common trigger factors were stress, sunlight exposure, flu. Higher body mass index was a probable risk factors for recurrence herpes labialis.